Spatial planning of Mount Bawakaraeng water source area. Issue 1 (October 2021) - Tandirerung Pasapan, Priya; Yunus, Muhammad; Saleng, Abrar; Susyanti Nur, Sri
Abstract: The challenge of utilization of the Mount Bawakaraeng area as a source of water supply for seven regencies/cities is to perform Spatial Planning of the Mount Bawakaraeng water source area. The aim of this study is to synchronize the laws and regulations related to spatial planning in Gowa regency with the cultural principles of the Makassar people, namely punna pangadakkan tena erokku, tena kulleku in realizing the law for spatial planning in the Mount Bawakaraeng water source area, based on the Adat Sampulo Rua. The research method used is normative research with philosophical and historical approaches. The results of the research showed that the spatial planning based on the Adat Sampulo Rua has not been implemented; the exclusion of adat/local community and the absence of unity within indigenous peoples as a unique system entity in the preparation of spatial planning are the causes. The area of Mount Bawakaraeng is an important ecosystem for the availability of raw water in South Sulawesi; community participation in developing the plan, utilization and control based on local wisdom is needed, so that spatial planning policies for the water source area have positive impact to the government and society.